State of the art postgraduate programs in Food Safety and Biotechnological Processes (FSBP) - Guevara Guerrero, Beatriz; Vásquez García, Andrea; Jurado Cortes, Norma (Revista Colombiana de Investigaciones Agroindustriales, 2022)
This article presents a reflection on the state of the art of university graduate programs in the disciplines of Food Safety and Biotechnological Food Processes (IPBA) and related academic training areas until 2021. It is part of the process of creation, design and development of a new program at the technological specialization level developed by the National Open and Distance University (UNAD) of Colombia. The search for systematic information was carried out through educational databases, listings that group graduate programs, search engines for graduate programs at the specialization level, technological specialization, master's degree, articles and documents from organizations working in IPBA. The objective of reviewing the state of the art of postgraduate programs in IPBA is to know what topics are being taught in universities at the national and global level in relation to the needs of food companies and industries and if there is a congruence between what is being taught academically at the national and global level and the requirements of the organizations. Therefore, postgraduate programs at national and international level were related, analyzing a low number of postgraduate programs with these characteristics and a great need for the creation of new postgraduate training programs in the area of food safety and biotechnological food processes.